Термодинамический анализ систем производства сахара - Мельник, Сергей Игоревич; Никульшин, Владимир Русланович; Денисова, Алла Евсеевна; Белоусов, Александр Валериевич (НТУ "ХПИ", 2018)
Проведен термодинамический анализ систем производства сахара на основе применения как Первого закона термодинамики (энергетические показатели), так и совместного применения Первого и Второго закона термодинамики (эксергетические показатели). На основании этого анализа сформированы три группы энергосберегающих опций: использующих вторичные энергоресурсы; изменяющих параметры энергоносителей; основанных на конструктивных компоновочных решениях (структурные изменения системы). Показано, что выявленные потенциалы энергосбережения могут служить основой для последующей оптимизации систем производства сахара, однако, окончательное решение о применении этих энергосберегающих подходов предполагает проведение термоэкономической оценки, поскольку реализация большинства из энергосберегающих опций требует существенных капитальных вложений.

Thermodynamic analysis of sugar production systems was carried out based on the application of the First Law of Thermodynamics (energy characteristics) as well as on the joint application of the First and Second Law of Thermodynamics (exergy characteristics). Based on this analysis, three groups of energy-saving options were formed: using waste energy resources; changing energy parameters; based on structural changes in the system. It is shown that the identified energy-saving potentials can serve as a basis for the subsequent optimization of sugar production systems. However, the final decision on the application of these energy-saving options requires a thermo-economic approach, since the implementation of most of them requires significant capital investment. The main exergetic characteristics of a typical sugar production scheme with a capacity of 3000 tons of sugar per day have been calculated, analysis of which showed that the main source of exergy losses (more than 70 %) in sugar production systems are the boiling processes, which also have a low degree of thermodynamic perfection (0.54). Losses of exergy in these processes as well as in others are caused by big heat fluxes and irreversibility of heat exchange processes at significant temperature drops, and as dissipative losses of centrifugation processes, mechanical separation, diffusion and transport of streams. The presented thermodynamic analysis is the basis for the subsequent thermo-economic optimization of sugar production systems
Thermodynamic analysis of sugar production systems
Keywords: энергосберегающие опции; эксергетические показатели; дифузионная установка; энергоресурсы; energy-saving options; exergy characteristics